Family Again! A Pregnancy that brought Hope - Akinsipe, Gbemisola (Spectrum Books Ltd, 2011)
Behold a time when girls fall, when they give their bodies to men and boys for mundane things such as money, popularity and fun, when families fall apart every minute and get really busy to tend to their girls. Lonke and her family are caught up in the web. They are at the verge of collapsing. Lonke, a girl just like any young girl gets pregnant at 16. Her mum's confidence in her is betrayed, her dad becomes tired and her brothers are taken away...
Keywords: Juvenile Fiction